Monitoring effects of atenolol versus olmesartan medoxomil on metabolic parameters - Singh, Ranjodh Jeet; Kohli, Kanika; Gupta, Parveen; Gupta, Ashwani Kumar (International Journal of Basic & Clinical Pharmacology, 2018)
Background: The increase in CVS morbidity and mortality could be significantly reduced by control of SBP and DBP, as well as reduction in Hyperlipidemia. Methods: The patients of stage-1 HTN with either sex according to JNC VII criteria were included and were followed up every 2 weeks from baseline upto 12 weeks. The randomized patients were divided into two groups to receive beta blocker viz. Atenolol 50 mg (group A, N=50) and ARB Olmesartan medoxomil 40 mg (group B, N=50). Results: The average Total cholesterol measured among Group A subjects was significantly increased by 1.8% by the end of 12th week whereas the average cholesterol measured among Group B subjects at baseline period was reduced by 7.9% after 12 weeks therapy. The average HDL measured among Group A subjects at baseline period significantly reduces by 5.9% by the end of 12th week whereas the HDL levels measured among Group B subjects at baseline period was significantly increased by after 12 weeks therapy. The average Triglyceride (TG) levels measured among Group A subjects at baseline period was significantly increased by 12.4% by the end of 12th week whereas the Triglyceride (TG) levels measured among Group B subjects at baseline period was significantly reduced by 9.5% after 12 weeks therapy. The average LDL levels measured among Group A subjects at baseline period was significantly increased by 1.5% by the end of 12thweek whereas the average LDL measured among Group B subjects at baseline period was significantly reduced by 11.2% to after 12 weeks therapy. The average VLDL levels measured among Group A subjects at baseline period was significantly increased by 12.4% by the end of 12th week whereas the average VLDL measured among Group B subjects at baseline period was significantly reduced by 9.5% after 12 weeks therapy. Conclusions: ARB- Olmesartan medoxomil is a better drug than beta blocker-Atenolol as it leads to greater deduction in lipid profile.